Effect of Indirect Neural Decompression Through Oblique Lateral Interbody Fusion for Degenerative Lumbar Disease. Issue 3 (1st February 2015) - Fujibayashi, Shunsuke; Hynes, Richard A.; Otsuki, Bungo; Kimura, Hiroaki; Takemoto, Mitsuru; Matsuda, Shuichi
<x xml:space="preserve">Abstract</x> Study Design. Prospective consecutive clinical study to assess the decompressive benefit and outcome of oblique lateral interbody fusion for lumbar degenerative diseases. Objective. To evaluate radiologically the effect of interbody distraction upon neural patency via an anterolateral retroperitoneal approach for the treatment of lumbar degenerative diseases. Summary of Background Data. Traditional treatment for symptomatic lumbar stenosis uses direct posterior decompression with or without fusion. Symptoms of radiculopathy and neurological claudication may also be alleviated indirectly through restoration of intervertebral and foraminal heights and correction of spinal alignment. Methods. Twenty-eight consecutive patients presenting with degenerative conditions that included concomitant lumbar stenosis underwent oblique lateral interbody fusion combined with percutaneous pedicle screw fixation at 52 lumbar levels without neuromonitoring. Magnetic resonance images were obtained successfully for 48 of 52 levels. The cross-sectional area of the thecal sac (CSA) was measured preoperatively and postoperatively on T2-weighted axial magnetic resonance images. Differences in CSA were compared, and the relationship between the ratio of CSA extension and that of the preoperative CSA was assessed. The change in disc height and segmental disc angle were measured. The relationships between CSA, disc height, segmental disc angle, and clinical results were assessed by correlational analysis. Results. Twenty-eight oblique lateral interbody fusions were performed successfully without neural complications. There was clinical improvement in all cases. The mean CSA increased from 99.6 mm2 preoperatively to 134.3 mm2 postoperatively (P < 0.001). The median CSA extension ratio was 30.2% and this correlated inversely with preoperative CSA. Disc height, segmental disc angle, and clinical results improved significantly. Multivariate regression analysis demonstrated that the preoperative CSA was the only independent factor that correlated inversely with the CSA extension ratio (corrected R2 = 0.361; P < 0.001). Conclusion. Spinal stenosis was resolved successfully by indirect decompression through a miniopen anterolateral retroperitoneal approach without the need for neuromonitoring. Level of Evidence: 3